Temporal evolution of submicron particles during extreme fireworks - Yadav S.K.; Kumar M.; Sharma Y.; Shukla P.; Singh R.S.; Banerjee T. (My University, 2025)
Evolution of submicron particles in terms of particle number concentration and mobility-equivalent diameter was measured during Diwali festival–specific intensive pyrotechnic displays in Varanasi over central Indo-Gangetic Plain (IGP). A scanning mobility particle sizer coupled with an optical particle sizer was used to fit in an overlapping size range, and particle number concentration was analyzed to have an insight into the new particle formation and subsequent evolution of particles from nucleation to accumulation mode. Further, variation in black carbon (BC) concentration and aerosol ionic composition was measured simultaneously. Frequent fluctuation in particle number concentration in and around Diwali festival was evidenced, primarily influenced by local emission sources and meteorology, with three distinct peaks in number concentrations (dN/dlogDp, 3.1–4.5 × 104 cm3) coinciding well with peak firework emission period (18:00–23:00 h). Submicron particle size distribution revealed a single peak covering a size range of 80–130 nm, and for all instances, number concentration maximum coincided with geometric mean minimum, indicating the emission primarily in the ultrafine range (< 0.1 μm). Interestingly, during peak firework emissions, besides rise in accumulation mode, an event of new particle formation was identified with increase in nucleation and small Aitken mode, before being dispersed to background aerosols. On an integral scale, a clear distinction was noted between a normal and an episodic event, with a definite shift in the formation of ultrafine particles compared with the accumulation mode. The BC diurnal profile was typical, with a prominent nocturnal peak (12.0 ± 3.9 μg m-3) corresponding to a decrease in the boundary layer height. A slight variation in maximum BC concentration (16.8 μg m-3) was noted in the night of the event coinciding well with firework emissions. An increase in some specific ionic species was also noted in combination with an increase in the overall cation to anion ratio, which was explained in terms of heterogeneous transformation of NOx and catalytic conversion of SO2. [Figure not available: see fulltext.]. © 2019, Springer Nature Switzerland AG.